Students perception of augmented reality learning media on solar system topics - Muhammad Andika Putra; Erman Erman; Enny Susiyawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
The purpose of this study was to describe students' perceptions of augmented reality learning media in solar system topics. The type of research used was descriptive research. The participants involved in this study were 32 students from class 8C of State Junior High School 3 Sidoarjo, Indonesia. The instruments used consist of a student perception questionnaire and an interview. The questionnaire has been validated previously and consists of 5 questions about the concept of planets and the concept of the moon concerning augmented reality learning media. The results showed indicators 1, 4, and 6 obtained the highest score of 97%. It means that students can easily understand these indicators using augmented reality. Indicator 2 got the lowest result of 72%, meaning that students have little difficulty understanding the indicator using augmented reality but are still in the good category. As many as 87% of students rated that augmented reality learning media is very helpful in understanding the material of the solar system. Data from interviews with six students also support this result. They stated that augmented reality is the most effective learning media in studying solar system topics because students considered it more transparent, more interesting, more comfortable to use, and more accessible for students to understand. In conclusion, augmented reality learning media has proven to be effectively used in learning solar system topics. It also can be applied to other abstract science topics that are difficult for students to find in everyday life.